Britain's Health Services (London : Communist Party of Great Britain)
1942-10 1942 1940s 40 pages Number of industrial accidents Number of new cases of disablement by accident in which compensation was paid (1937 figures):— Mines 139,230 Railways 18,176 Docks 9,861 Constructional work 9,658 Shipping 7,332 Quarries 6,861 Factories, etc. 218,532 409,650 Accident rate highest in heavy industry Iron and steel 11,108 cases per 100,000 employed. Constructional engineering 9,385 „ „ „ „ For all other manufacturing industry 2,642 „ „ „ „ Accident rate higher among young people than adults (1935 figures.) Per 100,000 employed: 4,352 cases among young people as against 3,410 adults (male). 1,414 „ „ „ „ „ „ 972 „ (female). Rising rate of accident - 40% increase reported from Birmingham since 1939. 1940 figures for factories and workshops reveal:— 45% increase in number of fatal accidents. 28.4% „ „ „ „ non-fatal accidents. Rising rate of industrial disease Notified cases of industrial dermatitis :— 1939 2,952 1940 4,744 Incidence of industrial (compensable) disease Per 100,000 men employed :— In mining 1,980 cases per annum; In factories 66 cases per annum. Industrial accident and disease aggravated by insufficient inspection 300 factory inspectors for 250,000 premises; Only one medical inspector for all mines and quarries — the most dangerous industry and one employing 750,000 men. THE ABOVE FACTS REPRESENT A CHALLENGE TO THE HEALTH SERVICES AND WORKERS. CAN IT BE MET? 36 15X/2/103/252